124,000 Attend ConExpo-Con/Agg ’99 in Las Vegas - Steve Kral (Society for Mining, Metallurgy & Exploration, 1999)
More than 124,000 people involved in the mining and construction industries throughout the world poured into Las Vegas, NV in March for ConExpo-Con/Agg ’99. Show organizers said this triennial exhibition is the largest equipment show in the Western Hemisphere and one of the largest exhibition of any industry. “Clearly, Con-Expo-Con/Agg ’99 was one of the largest trade shows of any industry ever held in the Western Hemisphere,” said Bruno Benna, co-chair of the event. Attendees included mining industry representatives, including aggregates, and sand and gravel producers. In addition, many of the attendees work in the construction, reclamation, forestry, asphalt paving, landscaping and concrete industries. According to show records, about 52% of those attending were company presidents, vice presidents, chief financial officers or managers.